2018
DOI: 10.1111/fwb.13114
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and reactivity continuum of dissolved organic matter in forested headwater catchments of Andean Patagonia

Abstract: Terrestrial inputs of dissolved organic matter (DOM) make a significant contribution to the carbon pool of headwaters and the reactivity of this pool depends on its source and diagenetic state, being influenced by photochemical and biological processes. The main goal of this study was to characterise the composition and reactivity of soil and leaf litter DOM from a native forest of Nothofagus pumilio (Nothofagaceae), and from natural stream water, evaluating the effect of degradation processes. Photo‐ and biod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…In fact, we did not measure a decrease in oxygen at 100% DOM soil , which suggests that the extracted DOM soil did not stimulate microbial activities. This is in line with studies from pelagic waters(Garcia et al, 2018;Hansen et al, 2016) and the oxic HZ(Wagner et al, 2014), which postulate that terrestrial DOM extracted from soils generally is less degraded in aquatic systems than DOM algal . By contrast,Fellman et al (2009) found high proportions of bioavailable DOC in the pore water of different soils, often exceeding those of the stream water.…”
supporting
confidence: 89%
“…In fact, we did not measure a decrease in oxygen at 100% DOM soil , which suggests that the extracted DOM soil did not stimulate microbial activities. This is in line with studies from pelagic waters(Garcia et al, 2018;Hansen et al, 2016) and the oxic HZ(Wagner et al, 2014), which postulate that terrestrial DOM extracted from soils generally is less degraded in aquatic systems than DOM algal . By contrast,Fellman et al (2009) found high proportions of bioavailable DOC in the pore water of different soils, often exceeding those of the stream water.…”
supporting
confidence: 89%
“…2011), and the leaching that occurs on inundation sends an initial pulse of DOC into the water column of wetlands. Accordingly, the initial DOM pool of FP showed optical signatures indicative of high humic content and prevalence of compounds of high molecular weight/size and aromaticity (Table S1), resembling terrigenous inputs (García et al . 2018).…”
Section: Resultsmentioning
confidence: 97%
“…Other investigations focusing on the photoreactivity of DOM in running waters and shallow permanent lakes in the same catchment have also reported high recalcitrance of the humic component C2 (or A+C peaks) (Soto Cárdenas et al . 2017; García et al . 2018).…”
Section: Resultsmentioning
confidence: 99%
“…S9†). 57 While these environmental associations can be made, PARAFAC components are statistically derived and do not have established, explicit chemical meaning for a given component. Further work is needed to do so.…”
Section: Resultsmentioning
confidence: 99%